Sex Reversal and Masculinization according to Growth in Longtooth Grouper Epinephelus bruneus - Oh, Seong-Rip (Dev Reprod, 2013)
To understand the sex reversal characteristics in the longtooth grouper (Epinephelus bruneus), this study examined the sex reversal and artificial masculinization of wild caught E. bruneus reared in indoor rearing tank after a 17α-methyltestosterone injection. To domesticate a broodstock, 64 wild caught E. bruneus, between 47.0 to 110.0 cm in total length and from 1.5 to 21.4 kg in body weight, were reared in indoor rearing tank (4.0 to 5.0 m wide, and 2.5 to 3.0 m depth) for four years. Seven specimens showed sex reversal from female to male during indoor rearing condition, whose total length and body weights were from 63.0 to 99.0 cm and from 4.4 to 13.2 kg, respectively. After inducing artificial masculinization in 14 female E. bruneus with a 17α-methyltestosterone (2.0 mg/kg BW) implants for 3 years, spermiation occurred in 9 specimens (total length: 54.0 to 68.0 cm, body weight: 2.3 to 4.3 kg). Among the female to male sex reversals, two specimens returned back to being female, whose body weights were 2.8 kg (initially 2.6 kg) and 2.7 kg (initially 2.3 kg). Therefore, this study suggested that E. bruneus (> 3.0 kg) was more effective in masculinizing by 17α-methyltestosterone implants.